The implication of corporate social responsibility on the strategic risk of the listed firms in Nigeria - Stephanie M. Chondough (ACRN Journal of Finance and Risk Perspectives (JOFRP), 2022)
This study focuses on the implications of corporate social responsibility (CSR) on the strategic risk of the listed financial and non-financial firms in Nigeria. The population of the study consists of 154 firms, while the census sampling technique was adopted to arrive at an adjusted population of 133. The correlation research design was implored using a positivism approach. Descriptive statistics, correlation matrix, multiple regression, confirmatory analysis and T-test were used to analyze the data extracted from the annual report. Hence, the result of the study shows that corporate social responsibility has a negative impact on strategic risk. The confirmatory factor analysis found that CSR engagement influences strategic risk (SRK), but to varying degrees, contradicting findings from the Frontier Model, PCSE, and GLS that both sectors will have similar results if they engage in CSR effectively. It is therefore suggested that the management of strategic risks need to be more integrated in corporate strategy as the capacity to listen to business stakeholders' viewpoints on social and environmental issues becomes a competitive need.
Keywords: 330; CSR; Strategic risk; Financial sector; Non-financial sector